Application of next generation sequencing in genetic counseling a case of a couple at risk of cystinosis - Mouna Ouhenach; Abdelali Zrhidri; Imane Cherkaoui Jaouad; Wiam Smaili; Abdelaziz Sefiani (BMC, 2020)
Abstract Background In Morocco, consanguinity rate is very high; which lead to an increase in the birth prevalence of infants with autosomal recessive disorders. Previously, it was difficult to diagnose rare autosomal recessive diseases. Next Generation Sequencing (NGS) techniques have considerably improved clinical diagnostics. A genetic diagnosis showing biallelic causative mutations is the requirement for targeted carrier testing in parents, prenatal and preimplantation genetic diagnosis in further pregnancies, and also for targeted premarital testing in future couples at risk of producing affected children by a known autosomal recessive disease. Methods In this report, we present our strategy to advise a future couple of first cousins, whose descendants would risk cystinosis; an autosomal recessive lysosomal disease caused by mutations in the CTNS gene. Indeed, our future husband's sister is clinically and biochemically diagnosed with cystinosis in early childhood. First, we opted to identify the patient's CTNS gene abnormality by using (NGS), then we searched for heterozygosity in the couple's DNA, which allows us to predict the exact risk of this familial disease in the future couple's offspring. Results We have shown that the future husband, brother of the patient is heterozygous for the familial mutation. On the other hand, his future wife did not inherit the familial mutation. Therefore, genetic counseling was reassuring for the risk of familial cystinosis in this couple's offspring. Conclusions We report in this study, one of the major applications of (NGS), an effective tool to improve clinical diagnosis and to provide the possibility of targeted premarital carrier testing in couples at risk.